Integrated multi-omics demonstrates enhanced antitumor efficacy of donafenib combined with FADS2 inhibition in hepatocellular carcinoma - Hui Li; Yafeng Dai; Di Wu; Song Gao; Jianhai Guo; Pengjun Zhang; Hui Chen; Fuxin Kou; Shaoxing Liu; Aiwei Feng; Baojiang Liu; Dongdong Hou; et al. (Translational Oncology)
Pharmacotherapy is crucial for advanced hepatocellular carcinoma (HCC). The multi-kinase inhibitor donafenib offers superior survival benefits over sorafenib. Donafenib has first-line status, but there is limited research for combination therapies with this anticancer agent. This study aimed to delineate donafenib's antitumor effects, including transcriptomics and proteomics to characterize gene expression changes in donafenib-treated HCC cell lines. In vitro and in vivo tumorigenicity studies were conducted to evaluate the combined antitumor effects of donafenib. Proteomic and transcriptomic analyses identified that donafenib downregulated fatty acid desaturase 2 (FADS2) at the protein and mRNA levels. In vitro and in vivo assays revealed an inhibitory effect of FADS2 blockade on HCC cell malignancy. The combination of donafenib and the FADS2 inhibitor sc-26,196 produced synergistic antitumor action, enhancing therapeutic efficacy in HCC cell lines and xenografted tumors in nude mice. These findings highlight the potential of FADS2 as a biomarker for HCC and show a promising combinatorial therapy for its treatment. Thus, we provide a theoretical basis for translating laboratory research into clinical applications.